A Case Study of Critical Thinking Cultivation Based on Social Cognitive Theory - Zhe, Guo (Journal of English Language and Literature (ISSN: 2368-2132), 2018)
How to cultivate critical thinking (CT) is considered as one of the most important goals of Chinese higher education over the years. However, many Chinese scholars have shown their concern on "CT Deficiency" after assessing CT skills of English majors in many universities. Thus, the affecting factors of CT development has been investigated from the perspective of the social cognitive theory by a detailed analysis of an English major with comparatively strong CT ability, attempting to find approaches to CT cultivation. After the qualitative analysis of reflection diaries and several interviews, the findings indicate that CT is shaped by the interaction of the environmental, individual and behavioural factors. Leaners can employ the strategies as interpretation, planning and implementation, self-regulation and adjustment, and reflection to facilitate the interaction